The Australian Work Exposures Study: Prevalence of Occupational Exposure to Formaldehyde - Driscoll, T.; Carey, Renee; Peters, S.; Glass, D.; Benke, G.; Reid, Alison; Fritschi, Lin (2015)
INTRODUCTION: The aims of this study were to produce a population-based estimate of the prevalence of work-related exposure to formaldehyde, to identify the main circumstances of exposure and to describe the use of workplace control measures designed to decrease those exposures. METHODS: The analysis used data from the Australian Workplace Exposures Study, a nationwide telephone survey, which investigated the current prevalence and exposure circumstances of work-related exposure to 38 known or suspected carcinogens, including formaldehyde, among Australian workers aged 18-65 years. Using the web-based tool OccIDEAS, semi-quantitative information was collected about exposures in the current job held by the respondent. Questions were addressed primarily at tasks undertaken rather than about self-reported exposures. RESULTS: Of the 4993 included respondents, 124 (2.5%) were identified as probably being exposed to formaldehyde in the course of their work [extrapolated to 2.6% of the Australian working population-265 000 (95% confidence interval 221 000-316 000) workers]. Most (87.1%) were male. About half worked in technical and trades occupations. In terms of industry, about half worked in the construction industry. The main circumstances of exposure were working with particle board or plywood typically through carpentry work, building maintenance, or sanding prior to painting; with the more common of other exposures circumstances being firefighters involved in fighting fires, fire overhaul, and clean-up or back-burning; and health workers using formaldehyde when sterilizing equipment or in a pathology laboratory setting. The use of control measures was inconsistent. CONCLUSION: Workers are exposed to formaldehyde in many different occupational circumstances. Information on the exposure circumstances can be used to support decisions on appropriate priorities for intervention and control of occupational exposure to formaldehyde, and estimates of burden of cancer arising from occupational exposure to formaldehyde.